Production of thymocyte-stimulating activity by cultured human thyroid epithelial cells. - Hirose, W (1987)
Since thyroid follicular epithelial cells (thyrocytes) have been shown to express a number of functions similar to monocytes, they were further examined for their potency in secreting thymocyte-stimulating activity (TSA). Although spontaneous production of TSA could not be detected when thyrocytes were cultured in the culture medium, TSA was demonstrated in the culture supernatants after stimulation with the immune adjuvant lentinan. The release of TSA was found in the culture supernatants collected 24 h after stimulation and was maintained for the 4 days of culture. Maximum levels of TSA release were achieved by 2 days. In addition, when culture supernatants of thyrocytes stimulated with lentinan or monocyte-derived interleukin 1 (IL-1) were incubated with a rabbit antibody to human IL-1, a parallel reduction in TSA was observed, suggesting that the active product in the thyrocyte culture supernatant shared a common antigenic site with IL-1. The demonstration of the production of IL-1 like activity by thyrocytes provides additional evidence that these cells, in addition to their functions as endocrine cells, may also participate in the local immune responses under appropriate conditions.